The Risk Assessment on Bamboo Weaving Craftsmen in Rajapolah District Tasikmalaya Regency - Isyeu Sriagustini; Teni Supriyani (The Indonesian Journal of Occupational Safety and Health, 2021)
Introduction: Tasikmalaya Regency is one of the areas in West Java that has a large industrial potential, especially small and handicraft industries. Every workplace, both formal and informal, has various potential hazards that can affect the health of workers or can cause occupational diseases. As bamboo is sharp, the craftsmen must be very careful in treating bamboo as a woven materialbecause the risk of accidents such as cutting off hands, being punctured by bamboo slats, and the risk of other potential mechanical hazards can occur. The purpose of this study is to analyze the occupational health and safety risks of woven craftsmen in the Rajapolah District, Tasikmalaya Regency. Methods: This study was a descriptive study. 5 Bamboo weaving craftsmen were the subjects of this study. Meanwhile, the objects of this study were the work process and workplace environment. Data collection was carried out by observation and interviews. Data analysis was performed using a semi-quantitative risk analysis method according to AS/NZS 4360: 2004 standard. Results: 23 potential hazards are identified from all stages of the bamboo process, and 23 health and safety risks are identified from all potential hazards, with 1 risk at a lowrisk level, 15 risks at a medium risk level, and7 risks at a highrisk level. Conclusion: There are 7 risks at the high-risk level that must be prioritized for control, originating from the potential hazards of ergonomics and chemicals.